COMPLEX FOOT INJURY TREATMENT USING VACUUM ASSISTED CLOSURE AND PLATELET-RICH FIBRIN METHOD – CASE REPORT - Petrović, Aleksandra; Čvorović, Luka; Korica, Stefan; Palibrk, Tomislav; Glišović Jovanović, Ivana (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Traffic accidents are one of the leading causes of death and injuries worldwide. According to the World Health Organization (WHO), more than 1.3 million people die annually in road accidents, while between 20 and 50 million suffer injuries. The majority of these injuries involve limb trauma, with the lower limbs being most commonly affected, particularly among pedestrians and motorcyclists.Case report: This report presents the case of a 77-year-old female pedestrian involved in a road accident, sustaining open fractures of the second and third metatarsal bones of the left foot (Gustilo type II). Initial surgical treatment was performed immediately after the injury, including extensive irrigation, debridement, and fracture stabilization using K-wires, along with below-knee plaster immobilization and triple antibiotic therapy. Further complex treatment involved a combination of vacuum-assisted closure (V.A.C.), platelet-rich fibrin (PRF) application, and hyperbaric oxygen therapy (HBO).Conclusion: Timely surgical intervention was crucial for achieving a positive outcome in an elderly patient, ensuring healing without infection and functional recovery. A multidisciplinary approach was essential in this complex case, adapting therapy to the specific needs of an elderly patient and improving overall recovery.
Keywords: open fracture; skin defect; hyperbaric oxygen therapy